Cannabis Use and Anxiety: Is Stress the Missing Piece of the Puzzle? - Temple, Elizabeth C.; Driver, Matthew; Brown, Rhonda F. (Frontiers in Psychiatry, 2014)
Objective: Comorbidity between anxiety and cannabis use is common yet the nature of the association between these conditions is not clear. Four theories were assessed, and a fifth hypothesis tested to determine if the misattribution of stress symptomology plays a role in the association between state-anxiety and cannabis. Methods: Three-hundred-sixteen participants ranging in age from 18-71 years completed a short online questionnaire asking about their history of cannabis use and symptoms of stress and anxiety. Results: Past and current cannabis users reported higher incidence of lifetime anxiety than participants who had never used cannabis, however these groups did not differ in state-anxiety, stress or age of onset of anxiety. State-anxiety and stress were not associated with frequency of cannabis use, but reported use to self-medicate for anxiety was positively associated with all three. Path analyses indicated two different associations between anxiety and cannabis use, pre-existing and high state-anxiety was associated with i) higher average levels of intoxication and, in turn, acute anxiety responses to cannabis use; ii) frequency of cannabis use via the mediating effects of stress and self-medication. Conclusions: None of the theories was fully supported by the findings. However, as cannabis users reporting self-medication for anxiety were found to be self-medicating stress symptomology, there was some support for the stress misattribution hypothesis. With reported self-medication for anxiety being the strongest predictor of frequency of use, it is suggested that researchers, clinicians and cannabis users pay greater attention to the overlap between stress and anxiety symptomology and the possible misinterpretation of these related but distinct conditions.